Innovative Technologies for the Protection of Historical Structures Against Earthquakes - Aras, Fuat (ICONARCH International Congress of Architecture and Planning, 2014)
Cultural heritage buildings are special structures and must be protected from natural disasters preserving at the same time their authenticity. In the seismic areas, one of the building classes that is consistently exposed to seismic risk is the one constituting the architectural heritage of the region. To minimize further destruction under future seismic activity it is necessary to reinforce the existing structures that are more vulnerable. As a consequence, new technological systems are needed, able to provide solution not only to specific structural or architectural problems, but also aiming at improving the global performance of the construction. Similarly, great attention is paid not only to reliability and durability of intervention methods, but also to the possibility to be easily monitored and removed if required, according to the widely shared policy, aiming at the safeguard of existing buildings, in particular in case of historical and monumental works, from inappropriate restoration operations. This study aims to represent innovative technologies and strategies to preserve the cultural heritage structures against earthquake effect. In particular, the application of fibre reinforced polymers and structural control systems are explained. Suitability of the strategies to architectural, historical and structural features and reversibility aspects are evaluated. As a case study the application of these strategies to a historical building in Istanbul is discussed.